Twenty-five women who shaped the Ottoman Empire - Miller, Ruth Austin, 1975- author. Link
1 online resource (xiv, 428 pages).
Keywords: "Twenty-Five Women Who Shaped the Ottoman Empire provides a tale of how women's failures as well as their triumphs, shaped a global society-not despite, but because of, gender. The Ottoman Empire was among the longest-lived polities in history, stretching between the thirteenth and twentieth centuries across three continents, several seas, and scores of cities, deserts, mountain ranges, rivers, and forests. This volume provides a compendium of idiosyncratic life stories and explores how women from the thirteenth century to the twentieth all across the globe understood the shape of the world in which they lived, and how they brought their consciousness of their gender to their efforts to re-shape it. Part One covers the women united by the feminist problem of their bodies as the restriction on their power. Part Two invokes historic feminist work on how women have negotiated and constructed the public and private spheres. Part Three covers women's speech and how it was mediated by men and male-dominated genres and institutions. Part Four looks at the traditional problem of women's reproductive bodies defined as vessels of collective political existence. And finally, Part Five explores the feminist writing on women as representative of death or decay. This book uncovers ordinary women and celebrated women, to women who failed, despite their best efforts, and to women who succeeded, to suicides or sex-workers as well as to queens, murderers, spies, witches, scientists and poets. This book is an accessibly offbeat feminist overview of the field of Ottoman History that provides students, scholars, general readers and non-specialists with an intriguing insight into how Ottoman women understood the pre-existing shape of the world in which they lived, and how they brought their consciousness of their gender into their efforts to re-shape this world"--